2018
DOI: 10.1016/j.ejor.2017.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimisation models for the travelling salesman problem with horizontal cooperation

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…When run, the program displays all paths leading to the initial solution under each objective and by using Python, the graphical illustration of the initial paths is given below. ; MinZ 2 = 467; MinZ 3 = 1879 which is same as the result obtained by Matthios Erghott [5], in his book multi criterion optimization (Second Edition, Springer) for his TSP tour (1,2,4,3,5,6,1). As the problem is about MOTSP, the decision maker can choose any of the compromised solutions depending upon his/her priority towards each objective.…”
Section: Multiobjective Traveling Salesman Problemsupporting
confidence: 71%
See 1 more Smart Citation
“…When run, the program displays all paths leading to the initial solution under each objective and by using Python, the graphical illustration of the initial paths is given below. ; MinZ 2 = 467; MinZ 3 = 1879 which is same as the result obtained by Matthios Erghott [5], in his book multi criterion optimization (Second Edition, Springer) for his TSP tour (1,2,4,3,5,6,1). As the problem is about MOTSP, the decision maker can choose any of the compromised solutions depending upon his/her priority towards each objective.…”
Section: Multiobjective Traveling Salesman Problemsupporting
confidence: 71%
“…Christof and Kenneth [1] described the major approaches to arrive at a solution for the users to choose from the partner efficiency approach and the coalition efficiency approach. While the former/latter benefits the logistics optimization model for interests in individual partner, however, here the individual partner has to set the objectives on its own set.…”
Section: Introductionmentioning
confidence: 99%
“…In Tricoire (2012), MDLS has been applied to several multi-objective problems such as the multi-objective multi-dimensional knapsack problem, the bi-objective set packing problem and the bi-objective orienteering problem. It has been later applied to intermodal train loading planning (Heggen et al, 2018) and several variants of the travelling salesman problem 60 (Defryn and Sörensen, 2018) and vehicle routing problems (Kovacs et al, 2015;Molenbruch et al, 2017;Lehuédé et al, 2019). A variant of the original MDLS, called Improved Multi-Directional Local Search (IMDLS) was proposed by Lian et al (2016).…”
Section: Meta-heuristic Reference Papersmentioning
confidence: 99%
“…Soysal et al (2018) studied a perishable food supply chain to assess the outcomes of horizontal collaboration in energy use (carbon emissions) and logistics cost based on Inventory Routing Problem (IRP) under single objective approach. Stellingwerf et al (2018) and Defryn and Sörensen (2018) were the only studies found evaluating the impact of shippers horizontal collaborative transport network considering multi-objective approach. Arango-serna et al (2018) proposed a genetic multi-objective model for the goods distribution optimization through collaborative inventory and transportation between several suppliers and customers.…”
Section: Introductionmentioning
confidence: 99%
“…were interested in the collaborative multiple centers vehicle routing problem with simultaneous delivery and pickup (CMCVRPSDP) to optimize operating cost and the total number of vehicles in Chongqing city's logistics. Defryn and Sörensen (2018) proposed a multi-objective optimization models for the travelling salesman problem with horizontal cooperation to combine the coalition economic objectives with individual partner ones. These cited works were studied using variants of Vehicle routing problem (VRP) supposing that facility location decisions have met in a prior step and cannot be modified.…”
Section: Introductionmentioning
confidence: 99%